Hubungan Motivasi Ibu dan Peran Kader dengan Kepatuhan Pemberian Vitamin A pada Balita di Posyandu Wilayah Kerja Puskesmas Dusun Baru V Koto Kabupaten Mukomuko Tahun 2025 - Refiani Natalia Damanik; Berlian Kando Sianipar; Yesi Putri (Jurnal Pakar Kesehatan, 2026)
Vitamin A deficiency is the leading cause of preventable childhood blindness and increases the risk of death from common childhood illnesses such as diarrhea. Regular high-dose vitamin A supplementation is a proven, low-cost intervention that has been shown to reduce all causes of mortality by 12 to 24%, and is therefore an important program in supporting efforts to reduce child mortality (UNICEF, 2025). The purpose of this study is to determine a correlation between maternal motivation and the role of health workers with vitamin A compliance in toddlers at Posyandu in the working area of Dusun Baru V Koto Health Center. This study used an analytical research design with a cross-sectional approach. Purposive sampling was employed, which involves selecting samples based on the researcher's considerations and in accordance with inclusion and exclusion criteria. The sample consisted of 75 mothers with toddlers. The results of the Chi-square test showed that the variable of Mother's Motivation and Compliance with Vitamin A Administration to Toddlers obtained a chi-square p-value of 0.001 (α<0.05), while the variable of Health Worker Role and Compliance with Vitamin A compliance to Toddlers obtained a chi-square p-value of 0.001 (α<0.05). Therefore, it can be concluded that there is a correlation between Maternal Motivation and the Role of health worker with Vitamin A Compliance in Toddlers at Posyandu in the Working Area of Dusun Baru V Koto Health Center. It is recommended that the health center improve health services, especially for maternal and children health.